Archaeology, nation and race - Greenberg, Raphael. (Cambridge ; New York)
xv, 218 sayfa
Keywords: “Archaeology, Nation, and Race is a must-read book for students of archaeology and adjacent fields. It demonstrates how archaeology and concepts of antiquity have shaped, and have been shaped by colonialism, race, and nationalism. Structured as a lucid and lively dialogue between two leading scholars, the volume compares modern Greece and modern Israel -- two prototypical and influential cases -- where archaeology sits at the very heart of the modern national imagination. Exchanging views on the foundational myths, moral economies, and racial prejudices in the field of archaeology and beyond, Hamilakis and Greenberg explore topics such as the colonial origins of national archaeologies, the crypto-colonization of the countries and their archaeologies, the role of archaeology as a process of purification, and the racialization and “whitening“ of Greece and Israel and their archaeological and material heritage. They conclude with a call for decolonization and the need to forge alliances with subjugated communities and new political movements.“ --